PERTENTANGAN NORMA FIKTIF NEGATIF DAN FIKTIF POSITIF SERTA KONTEKSTUALISASINYA MENURUT UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - Azza Azka Norra (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
The silence of the Government Administration has two possibilities, Tacit Refusal and Tacit Authorization. Tacit Refusal means that if the government agencies/bodies ignored requests from citizens then it is considered to have rejected the request. Tacit Authorization means if the government agencies/bodies ignored requests from citizens then it is considered to have granted the request. In Indonesia, both the Tacit Refusal and Tacit Authorization have their own places in the laws and regulations. The Law No. 5 of 1986 concerning Administrative Judiciary, rules the Tacit Refusal, meanwhile Law No. 30 of 2014 concerning Government Administration, rules the Tacit Authorization. Both cannot be implemented simultaneously because both of them are negating each other. This paper tries to explain the implementation of Tacit Refusal and Tacit Authorization after the enactment of Law No. 30 of 2014 concerning Government Administration in the administrative court.